Best approximation in b-modular spaces - Hiba Adel Jabbar; Samira Naji Kadhim; Salwa Salman Abed (مجلة بغداد للعلوم, 2024)
In this paper, some basic notions and facts in the b-modular space similar to those in the modular spaces as a type of generalization are given.  For example, concepts of convergence, best approximate, uniformly convexity etc. And then, two results about relation between semi compactness and approximation are proved which are used to prove a theorem on the existence of best approximation for a semi-compact subset of b-modular space.